Generation and in vivo characterization of a novel high-affinity human antibody targeting carcinoembryonic antigen - Louis Plüss; Frederik Peissert; Abdullah Elsayed; Giulia Rotta; Jonas Römer; Sheila Dakhel Plaza; Alessandra Villa; Emanuele Puca; Roberto De Luca; Annette Oxenius; Dario Neri (mAbs)
There are no effective treatment options for most patients with metastatic colorectal cancer (mCRC). mCRC remains a leading cause of tumor-related death, with a five-year survival rate of only 15%, highlighting the urgent need for novel pharmacological products. Current standard drugs are based on cytotoxic chemotherapy, VEGF inhibitors, EGFR antibodies, and multikinase inhibitors. The antibody-based delivery of pro-inflammatory cytokines provides a promising and differentiated strategy to improve the treatment outcome for mCRC patients. Here, we describe the generation of a novel fully human monoclonal antibody (termed F4) targeting the carcinoembryonic antigen (CEA), a tumor-associated antigen overexpressed in colorectal cancer and other malignancies. The F4 antibody was selected by antibody phage display technology after two rounds of affinity maturation. F4 in single-chain variable fragment format bound to CEA in surface plasmon resonance with an affinity of 7.7 nM. Flow cytometry and immunofluorescence on human cancer specimens confirmed binding to CEA-expressing cells. F4 selectively accumulated in CEA-positive tumors, as evidenced by two orthogonal in vivo biodistribution studies. Encouraged by these results, we genetically fused murine interleukin (IL) 12 to F4 in the single-chain diabody format. F4-IL12 exhibited potent antitumor activity in two murine models of colon cancer. Treatment with F4-IL12 led to an increased density of tumor-infiltrating lymphocytes and an upregulation of interferon γ expression by tumor-homing lymphocytes. These data suggest that the F4 antibody is an attractive delivery vehicle for targeted cancer therapy.